The relation of Echocardiographic findings to pulmonary Function tests in patients with Chronic obstructive Pulmonary Disease - Sultan, Kassim M.; Hussain, Muataz F.; Ismael, Ammar A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Chronic obstructive pulmonary disease (COPD) is a common disease and it accounts for over 10% of all hospital medical admission. Cigarette smoking is the most important risk factor. Pulmonary arterial hypertension (PHT) is a common complication of COPD and the increase in pulmonary artery pressure is often mild to moderate. The presence of pulmonary arterial pressure and its severity is readily and reliably determined by transthoracic echocardiography in majority of COPD patients. Patients and Methods: This study included 55 patients with mean age 65.6 ±8.2 years .The mean duration of symptoms was 18 ±10 months. 32 patients (58%) were current smoker, 18 patients (33%) were exsmoker and 5 patients (9%) were non smoker. The mean intensity of smoking for smoker was 49.5 ± 22.2 pack- years. For all patients, history, clinical examination, ECG, CXR, and routine blood tests were done. For all patients pulmonary function tests were done and patients were classified according to GOLD criteria into 4 stages. Echocardiography was done for all patients; ventricular and atrial dimensions were taken, and using Doppler technique to detect tricuspid and pulmonary regurgitation, estimation of pulmonary artery systolic and/or diastolic pressure using special formulas was undertaken. Results: Tricuspid regurgitation (TR) jet was found in 70.9% of patients with COPD. Increased pulmonary artery systolic pressure was found in 51% of patients with TR (36% of total patients) and increased pulmonary vascular resistance was found in 48.7% of patients with TR (34.5% of total patients). There were significant associations between echo findings of increasing RV size, TR, increased pulmonary arterial pressure and pulmonary vascular resistance with decrease in FEV1, FEV1/VC and oxygen saturation. There was no significant association with decrease in vital capacity. Conclusions: There is a high prevalence of pulmonary arterial hypertension with increasing severity of chronic obstructive pulmonary disease.